-6(1+q)=-72

Simple and best practice solution for -6(1+q)=-72 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(1+q)=-72 equation:


Simplifying
-6(1 + q) = -72
(1 * -6 + q * -6) = -72
(-6 + -6q) = -72

Solving
-6 + -6q = -72

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -6q = -72 + 6

Combine like terms: -6 + 6 = 0
0 + -6q = -72 + 6
-6q = -72 + 6

Combine like terms: -72 + 6 = -66
-6q = -66

Divide each side by '-6'.
q = 11

Simplifying
q = 11

See similar equations:

| 2/3z=-8 | | 60=7x+5y | | 11/12x7/8 | | 10t+8=-10+7t | | [y-4]+8=6 | | a+b=4a+b | | 96=6q+6q | | 11-14+10u=11u+16 | | 180=39+2x | | 4.50x=63.50 | | 4cos(2x)+cos(x)=0 | | 30+2X=4 | | r+10.4=12.6 | | x^2-6x+y^2+2y+44=0 | | Y-3/10=2/5 | | S=40*16+650 | | 10y-10=-5x | | 5(1)-14= | | 2x+3x=15+60 | | -n-4/9=1 | | 0.5+7802=287 | | 5(-115)-14= | | 15x+18y+33= | | L=54+4*32 | | 5(19)-14= | | -6n=-3-2 | | 2(x)=-2x+4 | | -28x-44=-20+38x+2 | | 2=6n-3 | | 6n=-3-2 | | 2x+10+4x+8=6x+18 | | 2(n+1)+3(2n-1)=15 |

Equations solver categories